The burrowing nematode of bananas Radopholus similis - Bridge, J.; Fogain R.; Speijer, P.R.; International Network for the Improvement of Banana and Plantain (1996)
Description of the banana nematode Radopholus similis (ecology, natural distribution, development cycle and pathotypes), the damage and losses that it causes and control methods (cultural, physical, chemical and genetic).